Who is Bill Gates? - Demuth, Patricia Brenna; Hammond, Ted (New York Grosset & Dunlap, An Imprint of Penguin Group (USA) Inc., 2013)
"Bill Gates, born in Seattle, Washington, in 1955, is an American business magnate, investor, philanthropist, and author. In this Who Was...? biography, children will learn of Gates' childhood passion for computer technology, which led him to revolutionize personal computers. Through the success of his now-world-famous software company, Microsoft, Bill Gates became one of the wealthiest philanthropists in history.This fascinating story of a child technology genius is sure to captivate any audience!"
Who is Bill Gates? -- Young thinker -- Lakeside whiz kid -- Learning a new language -- Opportunity knocks -- Microsoft is born! -- A big deal -- On the fast track -- Family life -- Facing challenges -- Sharing the wealth -- Life today.
Includes bibliographical references (pages 104) and index.
Age 8-12.
Keywords: Gates, Bill -- 1955- -- Juvenile literature; Businesspeople -- United States -- Biography -- Juvenile literature; Computer software industry -- United States -- History -- Juvenile literature